Acute Auricular Perichondritis With an Effusion - Agnes Usoro; Michael R. Ehmann (Clinical Practice and Cases in Emergency Medicine, 2019)
A 62-year-old man presented to the emergency department with acute, atraumatic, swelling of his left ear. Incision and drainage revealed serous fluid without blood or purulence. He was diagnosed with acute perichondritis with an effusion and managed with oral antibiotics. Perichondritis must be recognized and treated promptly to avoid necrosis of the underlying avascular cartilage and auricular deformity.